High relative abundance of firmicutes and increased TNF-α levels correlate with obesity in children - Yaneth C Orbe-Orihuela; Alfredo Lagunas-Martínez; Margarita Bahena-Román; Vicente Madrid-Marina; Kirvis Torres-Poveda; Eugenia Flores-Alfaro; Araceli Méndez-Padrón; Cinthya E Díaz-Benítez; Oscar Peralta-Zaragoza; Diana Antúnez-Ortiz; Miguel Cruz; Ana I Burguete-García (Instituto Nacional de Salud Pública, 2017)
Objective. To investigate the correlation among pro- or anti-inflammatory cytokines and the two main gut microbiota phyla in obese children. Materials and methods. Anthropometric data were obtained from 890 children under 14 years old to determine the degree of obesity. Serum cytokine concentration was measured by ELISA. Relative abundance of gut microbiota in feces was evaluated by quantitative RealTime PCR assays. Results. Anthropometric and biochemical parameters were statistically higher in overweigth/ obese children (OW/O) than in lean (NW), Increased TNF-α levels were found in obese children that also have a high relative abundance of Firmicutes. Conclusions. Obese children have a high relative abundance of Firmicutes that correlates with increased levels of TNF-α. This is the first study that shows a relation between Firmicute abundance and TNF-α serum concentration in obese children.